Anatomical compatibility of avocado grafting at different scion growth stages - RAMDAN HIDAYAT; ANTONIA JESSICA SHERLYN DA COSTA; JULI SANTOSO PIKIR; MUHAMMAD RIZKY ROMADHON; OKKY TALITHA; TILMIIDZAH SALMA FATHIN (Smujo International, 2026)
Abstract. Hidayat R, Da Costa AJS, Pikir JS, Romadhon MR, Talitha O, Fathin TS. 2026. Anatomical compatibility of avocado grafting at different scion growth stages. Asian J Agric 10 (1): g100131. https://doi.org/10.13057/asianjagric/g100131. This research aimed to evaluate the effectiveness of three grafting methods: cleft, wedge, and splice combined with three scion physiological stages: flushing (10 days after shoot emergence), endodormancy (30 days), and ecodormancy (50 days). The experiment assessed graft success in terms of survival rate, bud break duration, leaf production, flush interval, and vascular tissue compatibility. The splice grafting method using scions at the ecodormancy stage yielded the highest graft survival (72.50%), significantly outperforming other combinations. This treatment also achieved the earliest bud break (6.17 days), produced the most leaves (8.92 leaves per scion), and exhibited the shortest flush interval. Microscopic analysis at 45 and 60 days after grafting (DAG), using an Olympus CX21 binocular microscope equipped with an Optilab camera, revealed superior tissue compatibility in this treatment, characterized by minimal necrosis and successful union of xylem and phloem between the rootstock and scion. It is the first study to integrate physiological scion staging with histological validation of graft compatibility in avocado (Persea americana). These findings demonstrate that splice grafting with ecodormant scions significantly enhances morphological performance and vascular integration, providing a practical and scientifically supported protocol for improving avocado propagation in tropical highland conditions.